Is "Ethnic Democracy" Really Possible? Jews, Arabs and the Israeli Regime (جماعة, 2025)
In this essay we present a critique of the "ethnic democracy" model, formulated by political sociologist Sammy Smooha, to account for Israel's political structure and for relations between Jews and Arabs. On a broader level, we also aim to challenge the unproblematic acceptance of Israel as a democracy by most scholars in the field. While the "ethnic democracy" model has been adopted by a number of Israeli scholars, and while "democracy" is itself a contested concept, our analysis exposes several serious analytical problems. These point to a case of "conceptual stretching" in the current use of the model for classifying the Israeli regime. The Israeli regime implements a range of laws, policies and practices which contravene the basic tenets of democracy: it differentiates legally between citizens on the basis of their ethnic-nationality; exposes the minority to tyranny of the majority; maintains fuzzy political and territorial borders which undermine the concept of the "demos"; and applies a range of discriminatory policies towards Israel's Paletinian-Arab citizens. Further, Smooha, like most scholars in the field, overlooks the structural Judaization process which stands at the base of the Israeli ethnocratic regime. This process constantly changes the demographic, geographic and political relations in Israel/Palestine in favor of Jews. We contend that such a regime cannot be classified as a "democracy", thereby casting doubt over the theoretical and empirical credibility of the "ethnic democracy" model.